Joint Evaluation of Employment Guarantee Scheme of Maharashtra Second Paper State Level Information on the Employment Guarantee Scheme in Maharashtra State - Planning Commission (Planning Commission, 1976)
The State of Maharashtra forms a major part of peninsular India on the western side with the total area equal to approximately 10% of the area of the country. The State is entirely situated within the tropics. Historically the State has been composed of three regions, namely Western Maharashtra, Vidarbha and Marathwada. Administratively it is divided into four divisions and 26 districts. The population of Maharashtra State according to the 1971 census is 5 .04 crores. This population lives in 289 towns (including cities) and 35,778 inhabited villages (Greater Bombay excluded) spread over 235 talukas of the 25 districts.
Programme Evaluation Organisation, Planning Commission, Government of India, Directorate of Economics and Statistics, Government of Maharashtra